Pemodelan Sistem Informasi Order Fullfillment Pada Perusahaan Diesel Menggunakan Enterprise Architecture Planning Archimate - Nirwan Nirwan; Johanes Fernandes Andry (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
A diesel company that currently has three business segments: marine engines, industrial machinery and industrial generating sets. For the wider public, this diesel company is very popular in marine engines and is a world-leading innovation, such as Aquamatic drives and counter-rotating propellers, Duoprop. This diesel company is able to create high-tech products and support the global market of industries, such as diesel-operated generators, cranes and container handlers. This company has seen good business prospects for the company in the future. For the East Asia region, the head office uses Singapore to manage business operations including as warehouse area, sales and marketing activities. The more rapid competition becomes the impact of competitors, the first problem identified in this study will be mapping application planning to support the needs of existing corporate governance through enterprise architecture planning. The method used to plan the entire system will use archimate modeling, included are business, application and technology layer which will produce modeling order fulfillment applications. In this problem, the focus will be on application development factors that can help optimize business process problems such as: inputting data activities, competencies and responsibilities, time, constraints and technical documentation, standards applied, reports produced for various decision-making processes, internal communication and external, and other resources. These problems can enable the implementation of enterprise architecture methods into the company by using and managing data into enterprise architecture analysis and project planning for marketing strategies, corporate architectural analysis patterns are expected to overcome the company's problems.